Job Design and Skill Developments in the Workplace - Giovanni Russo (Institute for the Study of Labor (IZA), 2016)
We investigate the relationship between job complexity and the skills development of adult workers in Europe using the Cedefop European Skills and Jobs Survey (ESJS). The results suggest that challenging workplaces, workplaces in which jobs are designed to include complex tasks, and which place high demands on workers' skills, also stimulate workers' skills development. Increasing the degree of job complexity has positive and robust effects on the degree of skill development, and so does an increase in work experience (tenure). The analysis stresses the importance of on-the-job learning and contextual workplace characteristics for adult workers' skills development.
Keywords: J24; 330; job characteristics; job complexity; skills; skills development; learning